The determinants of household debt in Malaysia / Nur Raihan Mohd Nasir - Mohd Nasir, Nur Raihan (2016)
Household debt has always been an attentive issue to every country around the world. The issue of household debt in Malaysia start to be serious issue since 2000 and it seems like there is no end. The aim of this paper is to examine the determinant of Malaysian household debt. In this research, the data that used for the period 39 quartiles starting 2006 until 2015 which is that had collect from Data Stream. Multiple linear regression models have been used to determine relationship and significantly between household debt (HHD) as a dependent variables then household income (HINC), housing price (HPI) and interest rates (IR) as an independents variables. This paper found that housing price is determinant of household debt, where there is significantly influence household debt. From the results, household income, housing price and interest rates contribute positive relationship to the household debt in Malaysia.